2018
DOI: 10.3389/fendo.2018.00638
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Related Lipohypertrophy: Lipogenic Action or Tissue Trauma?

Abstract: Lipohypertrophy has been suggested as an outcome of lipogenic action of insulin and/or injection-related tissue trauma. In a cross-sectional study, we evaluated the predictors of lipohypertrophy in 372 type 1 diabetes patients (mean age 17.1 years) receiving subcutaneous insulin with pen and/or syringes for ≥3 months. On examining injection sites with inspection and palpation technique, 62.1% patients demonstrated lipohypertrophy. Univariate analysis showed that gender, BMI, HbA1c, injection device, rotation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
2
26
1
4
Order By: Relevance
“…Also, as our patients only used insulin analogs, we could not compare LH rates associated with them to those associated with human regular, NPH, or premixed insulin preparations, which often were used instead, in studies published by other investigators. However, many studies found no significant differences among the types of insulin concerning the association with LHs [43][44][45][46][47][48].…”
Section: Limitationsmentioning
confidence: 99%
“…Also, as our patients only used insulin analogs, we could not compare LH rates associated with them to those associated with human regular, NPH, or premixed insulin preparations, which often were used instead, in studies published by other investigators. However, many studies found no significant differences among the types of insulin concerning the association with LHs [43][44][45][46][47][48].…”
Section: Limitationsmentioning
confidence: 99%
“…Insulin therapy may cause LH due to lipogenic action and/or injection‐related tissue trauma with repeated administration in the same site . The prevalence of LH is reported at 37% .…”
Section: Reportmentioning
confidence: 99%
“…A recent audit from India [3] reported a much lower prevalence at 12.5% of all insulin users although this was a retrospective collection of cases based only on clinical examination and could be an underestimate while another survey [4] on injection technique found that based on a physical examination by nurses, one in five diabetic patients on insulin had LH. Two recent studies [5,6] from India reported that more than 60% of the patients developed LH. Lipohypertrophy was found to be more prevalent in obese patients and those with hypoglycemia and higher HbA1C [7].…”
mentioning
confidence: 99%
“…LH which appears as a rubbery swelling in the subcutaneous (SC) tissue at injecting sites is believed to develop secondary to the lipogenic action of insulin or to the trauma related to injections [5]. Various factors reported to be associated with a greater risk of LH in diabetic patients include longer duration of insulin use, failure to injection site rotation, needle reuse [4], longer needles, longer duration of diabetes [7,8], low BMI, total daily dose of insulin, twice daily insulin regimen, the use of conventional insulins compared with analogues [5], and poor glycemic control [8,9]. It has been shown that the risk of LH with insulin reuse is substantially higher than those who do not reuse.…”
mentioning
confidence: 99%
See 1 more Smart Citation